Deep learning model of hiss waves in the plasmasphere and plumes and their effects on radiation belt electrons - Huang, Sheng; Li, Wen; Ma, Qianli; Shen, Xiao-Chen; Capannolo, Luisa; Hanzelka, Miroslav; Chu, Xiangning; Ma, Donglai; Bortnik, Jacob; Wing, Simon (Frontiers in Astronomy and Space Sciences, 2023)
Hiss waves play an important role in removing energetic electrons from Earth's radiation belts by precipitating them into the upper atmosphere. Compared to plasmaspheric hiss that has been studied extensively, the evolution and effects of plume hiss are less understood due to the challenge of obtaining their global observations at high cadence. In this study, we use a neural network approach to model the global evolution of both the total electron density and the hiss wave amplitudes in the plasmasphere and plume. After describing the model development, we apply the model to a storm event that occurred on 14 May 2019 and find that the hiss wave amplitude first increased at dawn and then shifted towards dusk, where it was further excited within a narrow region of high density, namely a plasmaspheric plume. During the recovery phase of the storm, the plume rotated and wrapped around Earth, while the hiss wave amplitude decayed quickly over the nightside. Moreover, we simulated the overall energetic electron evolution during this storm event, and the simulated flux decay rate agrees well with the observations. By separating the modeled plasmaspheric and plume hiss waves, we quantified the effect of plume hiss on energetic electron dynamics. Our simulation demonstrates that, under relatively quiet geomagnetic conditions, the region with plume hiss can vary from L=4 to 6 and can account for up to an 80% decrease in electron fluxes at hundreds of keV at L>4 over three days. This study highlights the importance of including the dynamic hiss distribution in future simulations of radiation belt electron dynamics.